Agreement between the EWGSOP2 and SDOC consensuses for sarcopenia in patients receiving hemodialysis: Findings of a cross sectional analysis from the SARC-HD study - Duarte, Marvery P.; Nóbrega, Otávio T.; Baião, Victor M.; Vieira, Fábio A.; Monteiro, Jacqueline S.; Pereira, Marina S.; Pires, Luis F.; Queiroz, Gabrielle G.; Silva, Mauro J.; Silva, Maryanne Z. C. [UNESP]; Costa, Fabiana L. [UNESP]; Disessa, Henrique S. [UNESP]; et al. (Wiley, 2024)
Background: Differences in definitions and operational diagnoses for sarcopenia create difficulties in understanding the epidemiology of the disease. We examined the prevalences of sarcopenia using the revised European Working Group on Sarcopenia in Older People (EWGSOP2) and the Sarcopenia Definitions and Outcomes Consortium (SDOC) consensuses and analyzed their level of agreement in patients receiving hemodialysis. Methods: Data from the SARCopenia trajectories and associations with clinical outcomes in patients receiving hemodialysis (SARC-HD) multicenter study in Brazil were analyzed. Muscle strength was assessed using handgrip strength, muscle mass by calf circumference, and physical performance by the 4-m gait speed test. Sarcopenia was diagnosed according to both the EWGSOP2 (low muscle strength plus low muscle mass) and the SDOC (low muscle strength plus low physical performance). The Cohen kappa statistic was used to determine the level of agreement between the consensuses. Results: 838 patients (57.8 ± 15.0 years; 61% men) from 19 dialysis units were included. We found similar prevalences of sarcopenia between the consensuses (EWGSOP2, n = 128, 15.3%; SDOC, n = 105, 12.5%) but with weak agreement (50 of 233 patients, 21.5%; κ = 0.34, 95% CI 0.25–0.43). Agreement was also weak within age categories (≥60 years, κ = 0.34; <60 years, κ = 0.15; both P < 0.001). Of the 51 patients diagnosed by the EWGSOP2 criterion as having severe sarcopenia, all but 1 (98.0%) met the SDOC criterion for sarcopenia (κ = 0.61, 95% CI 0.52–0.70). Low muscle strength was more frequently diagnosed using the SDOC than with the EWGSOP2 (52.3% vs 25.9%). Conclusion: We found a weak agreement between the EWGSOP2 and SDOC consensuses for the diagnosis of sarcopenia in patients receiving hemodialysis. Although still weak, agreement was marginally better for older patients. These findings highlight the importance of a global and standardized conceptual diagnosis of sarcopenia.
Keywords: calf circumference; chronic kidney disease; dialysis; handgrip strength; sarcopenia